Pre-Commercial Procurement: In Search of Innovative Solutions for the Public Sector - Pavlova, Miglena; Dimitrova, Petya; Vasileva, Kristina (Research Papers, 2023)
Public sector expenditures in the form of public procurement form 14% of the gross domestic product of the European Union. Realizing the potential of this impressive purchasing power determines the direction of building new concepts in the procurement process. A strategic understanding of procurement hat shifts the focus from “how” we buy to “what” we buy is outlining. Innovative procurement is one aspect of the strategic concept for this peculiar relationship between the public and private sectors. Pre-commercial procurement as an approach to purchase innovative solutions in response to identified needs of the public sector adds value not only in terms of buyers, but also to achieve economic growth by creating competition in the market, accelerated commercialization of innovative solutions, improvement of cooperation between market entities, incl. cross-border etc.